Drug Allergy Clinical Characteristics in Pediatrics - Almira, R. Devina Fathia; Sapartini, Gartika; Dewi, Vycke Yunivita Kusumah (Althea Medical Journal, 2017)
Background: A drug allergy causes a morbidity and a mortality due to its various range of clinical manifestation. Unfortunately, a studyÂ focusing in pediatric drug allergy is insufficient, especially in Bandung. Thus, this study is conducted to determine the clinical characteristic of pediatric drug allergy in Dr. Hasan Sadikin General Hospital Bandung.Methods: This study was a retrospective descriptive study using medical records of pediatric drug allergy patients between 2010â2015 in Dr. Hasan Sadikin General Hospital Bandung taken with total sampling method. The variables were patient age, gender, causative drug, and clinical manifestation. Clinical manifestation was then divided into exanthem, urticaria, erythema multiforme, Steven-Johnsonâs syndrome/toxic epidemiolytic necrosis (SJS/TEN), and fixed drug eruption (FDE). Results: Out of 101 patients, only 71 were included in the study due to incomplete medical records of the rest. There were 34 (47.89%) males and 37 (52.11%) females. Patientsâ age ranged from 1â18 years old with the mean of 7.4 years old. The most common clinical manifestation was SJS/TEN with 25 (35.21%) patients, followed by exanthem with 22 (30.98%) patients. The most common suspected causative drug was non-steriodal anti inflammatory drugs (NSAID) (24%), followed with penicillin (21%).Conclusions: Most common manifestation of pediatric drug allergy in female is SJS/TEN, meanwhile in male is exanthema. Steven-Johnsonâs syndrome/toxic epidemiolytic necrosis mostly occurs at the age group of 12â18 years old, and exanthema at the age group of 0â3 years old. This condition is mostly caused by NSAID and penicillin.DOI:Â 10.15850/amj.v4n2.1097